Inflammatory myofibroblastic tumour of the urinary bladder: the role of immunoglobulin G4 and the comparison of two immunohistochemical antibodies and fluorescence in‐situ hybridization for the detection of anaplastic lymphoma kinase alterations. Issue 1 (29th January 2015) - Choi, Euna; Williamson, Sean R; Montironi, Rodolfo; Zhang, Shaobo; Wang, Mingsheng; Eble, John N; Grignon, David J; Lopez‐Beltran, Antonio; Idrees, Muhammad T; Baldridge, Lee Ann; Scarpelli, Marina; Jones, Carol L; et al.
<x xml:space="preserve">Abstract</x> Aims We examined gene rearrangement and the expression of anaplastic lymphoma kinase (ALK) in urinary bladder inflammatory myofibroblastic tumour (IMT) using fluorescence in‐situ hybridization (FISH) and two immunohistochemical antibodies to ALK. We also investigated whether IMT represents an immunoglobulin (Ig)G4‐related disease. Methods and results The performance of the Dako FLEX ALK monoclonal antibody (CD246) and the Cell Signaling Technology ALK (D5F3) XP monoclonal antibody were compared. Overall, 11 of 16 tumours showed ALK expression by immunohistochemistry (69%). Ten demonstrated ALK expression with both stains and one was positive with D5F3 but not CD246 (91% correlation). The D5F3 antibody yielded a stronger staining intensity and a higher sensitivity. Nine tumours demonstrated ALK rearrangements (56%) by FISH. Three were ALK+ by immunohistochemistry but negative for rearrangement by FISH, whereas one showed rearrangement by FISH but was negative by immunohistochemistry. In total, 12 tumours were positive for ALK abnormalities (75%). Using current criteria, no cases were classified as an IgG4‐related disease. Conclusions The ALK D5F3 immunohistochemical stain showed superior staining characteristics compared with ALK CD246. Discrepancies in the results between FISH and immunohistochemistry for ALK abnormalities may have causes that are multifactorial. By current criteria, IMT does not represent an IgG4‐related disease.